Advances in Photonic and Plasmonic Nanomaterials - Nikolaos G. Semaltianos (Nanomaterials)
Nanomaterials and nanostructures with different morphologies or geometrical shapes that exploit plasmons, and particularly surface plasmon polaritons, are useful for a wide range device fabrication-related applications [...]